These tangled vines : a novel - MacLean, Julianne (Lake Union Publishing, 2021)
"Fiona travels to Italy, where the family is shocked to learn of her existence and desperate to contest her share of the will. While the mystery of her mother's affair is slowly unraveled, Fiona must navigate through tricky family relationships and tense sibling rivalries. Fiona both fears and embraces her new destiny as she searches for the truth about the fateful summer her mother spent in Italy and the father she never knew." -- Amazon.com